Payment system technologies and functions : innovations and developments - Nakajima, Masashi, 1958- (Hershey, PA : Business Science Reference, 2011)
'This book analyzes the evolutionary trends, functions and mechanisms of payment systems and presents an in-depth explanation of how these trends led to the reduction of settlement risk and the importance of such mechanisms that have contributed to the evolutionary progress of payment systems'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Check collection systems; Electronic funds transfers; Clearinghouses (Banking).; Payment; Payment systems